2021
DOI: 10.3389/frai.2021.663190
|View full text |Cite
|
Sign up to set email alerts
|

Robot Gaze Behavior Affects Honesty in Human-Robot Interaction

Abstract: As the use of humanoid robots proliferates, an increasing amount of people may find themselves face-to-“face” with a robot in everyday life. Although there is a plethora of information available on facial social cues and how we interpret them in the field of human-human social interaction, we cannot assume that these findings flawlessly transfer to human-robot interaction. Therefore, more research on facial cues in human-robot interaction is required. This study investigated deception in human-robot interactio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…With full experimental control, we explored neural correlations of human-robot interactions in an ecologically valid setup (Matusz et al, 2019;Czeszumski et al, 2020;Nastase et al, 2020). There is vast literature on the topic of joint actions between humans and robot partners (Curioni et al, 2019a;Schellen et al, 2021;Wahn and Kingstone, 2021). Neural markers of action monitoring during human-robot interactions were studied in turn-taking tasks and utilized for brain-computer interfaces to improve communication between robots and humans Cheng, 2018, 2019a,b).…”
Section: Discussionmentioning
confidence: 99%
“…With full experimental control, we explored neural correlations of human-robot interactions in an ecologically valid setup (Matusz et al, 2019;Czeszumski et al, 2020;Nastase et al, 2020). There is vast literature on the topic of joint actions between humans and robot partners (Curioni et al, 2019a;Schellen et al, 2021;Wahn and Kingstone, 2021). Neural markers of action monitoring during human-robot interactions were studied in turn-taking tasks and utilized for brain-computer interfaces to improve communication between robots and humans Cheng, 2018, 2019a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies were found that considered the human factor with RPA in depth. Our literature search for related studies addressed the area of Human-Robot Interaction (HRI), which studies the interaction between robots and humans (Fontanillo Lopez et al, 2020;Schellen et al, 2021). Although the subject of relationship between humans and automata is not new, the study of HRI became more prominent in the 1980s, when behavior-based robotics started using distributed sense-response loops to generate appropriate responses to external stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The decision-making task was related to giving honest or deceptive feedback to iCub. The authors found that fewer deception choices occurred after trials in which iCub established mutual gaze as a feedback ( Schellen, Bossi, & Wykowska, 2021 ). In a recent EEG study, Kompatsiari and colleagues examined oscillatory brain response to mutual and averted gaze established by the iCub robot during an attentional cuing task ( Kompatsiari, Bossi, & Wykowska, 2021 ).…”
Section: Introductionmentioning
confidence: 99%